The Influence of the Family Hope Program and Direct Cash Assistance on Community Poverty Levels: A Quantitative Study - Mustapa, Nur Indah; Panigoro, Meyko; Gani, Imam Prawiranegara; Mahmud, Melizubaida; Halid, Risca Marsanti (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
The purpose of this study is to determine whether there is an influence of the Family Hope Program (PKH) and Direct Cash Assistance (BLT) on the poverty level of the community in Poowo Barat Village, Kabila District, Bone Bolango Regency. This research uses a descriptive quantitative approach. The sample size is 63 respondents, namely recipients of the Family Hope Program and recipients of Direct Cash Assistance. Data collection techniques were obtained from observations and questionnaires. The data analysis technique used is multiple linear regression analysis. The results showed that simultaneously, the Family Hope Program (PKH) and Direct Cash Assistance (BLT) variables have a significant effect on the poverty level of the community in Poowo Barat Village, Kabila District, Bone Bolango Regency. From the results of data analysis in the table above, the R value is 0.520 and R Square is 0.271. This means that the regression model obtained can explain that the Family Hope Program (X1) and Direct Cash Assistance (X2) variables can influence the poverty level of the community in Poowo Barat Village, Kabila District, Bone Bolango Regency by 27.1%. While the remainder is influenced by other variables not examined in this study.